Durvalumab After Chemoradiation for Unresectable Stage III Non-Small Cell Lung Cancer: Inferior Outcomes and Lack of Health Equity in Hispanic Patients Treated With PACIFIC Protocol (LA1-CLICaP) - Raez, Luis E.; Arrieta, Oscar; Chamorro, Diego F.; Soberanis-Piña, Pamela Denisse; Corrales, Luis; Martín, Claudio; Cuello, Mauricio; Samtani, Suraj; Recondo, Gonzalo; Mas, Luis; Zatarain-Barrón, Zyanya Lucia; Ruíz-Patiño, Alejandro; et al. (Frontiers in Oncology, 2022)
Objectives: Compare rate disparity between outcomes (overall survival (OS), progression-free survival (PFS), and safety) of concurrent chemoradiation (cCRT) followed by durvalumab (PACIFIC) in two patient cohorts with locally advanced (LA) stage III (SIII) non-small cell lung cancer (NSCLC), one non-Hispanic White (NHW), and the other Latin-American. Methods: A multicenter retrospective study was performed, including 80 Hispanic and 45 NWW LA SIII NSCLC patients treated with cCRT followed by durvalumab. Both cohorts were analyzed in terms of OS, PFS, and safety and compared between them and with the PACIFIC trial population. The efficacy-effectiveness gap was assessed using an efficacy-effectiveness (EE) factor. In both cohorts, results of PDL-1 testing were recorded, and the main outcomes were compared according to PD-1 expression levels. Results: For the entire population (N=125), the overall response rate (ORR) was 57.6% (N=72), and 18.4% (N=25) achieved stable disease. OS was 26.3m (95%CI 23.9-28.6), and PFS was 20.5m (95%CI 18.0-23.0). PFS assessed by ethnicity showed a median for Hispanics of 19.4m (95%CI 16.4-22.5) and 21.2m (95%CI 17.2-23.3; p=0.76) for the NHW group. OS by race showed a significant difference in favor of the NHW group, with a median OS of 27.7m (95%CI 24.6-30.9) vs. 20.0m (95%CI 16.4-23.5) for Hispanics. (P=0.032). Unadjusted 12-m and 24-mOS was 86.6% (95%CI 79.9–88.0) and 46.6% (95%CI 40.2–48.3) for NHW compared to 82.5% (95%CI 77.1–84.2) and 17.5% (95 %CI 15.6-24.5) in Hispanics. NHWs had an EE factor of 0.78 and Hispanics had 0.58, showing a reduction in survival versus NHWs and PACIFIC of 20% and 42%, respectively. HR for the OS among NHWs and Hispanics was 1.53 (95%CI 1.12-1.71; P=0.052) and 2.31 (95%CI 1.76-2.49; P=0.004). Fifty-six patients (44.8%) had some degree of pneumonitis due to cCRT plus durvalumab. There was no difference in pneumonitis according to race (P=0.95). Conclusions: Among patients with SIII NSCLC, NHW has better survival outcomes when compared to Hispanics, with an OS that seems to favor the NHW population and with an EE factor that shows a shorter survival in Hispanics compared with NHW and with the PACIFIC trial group.